Rethinking three decades of decentralisation in Ghana’s local government administration under the Fourth Republic - Fobih, Nick (Advances in Social Sciences Research Journal, 2020)
The purpose of this paper is to investigate the successes and challenges facing Ghana’s decentralisation programme. Within the thirty years of the implementation of decentralisation in Ghana, there have been some major changes, successes, and challenges that are worth investigating to determine whether successive governments in the Fourth Republic have made significant progress in the three decades or whether there is a need to do more to strengthen the country’s decentralisation programme. The study examined different decentralisation literature to assess the performance of the country’s decentralisation programme. The methodology used is based on the qualitative approach and the descriptive method. Our findings show that regardless of the in-roads made since in the thirty years Ghana’s decentralisation programme, a myriad of challenges make its implementation complex, and its full potential impact on citizens and the local communities not realized. The significance of the study is that the outlined challenges and recommendations will inform national policy makers and the local government administrators to take Ghana’s decentralisation reforms a step further towards realizing the ultimate goals of the programme. This study further contributes toward academic discussions on decentraliaation in Ghana and Africa in general.